2002
DOI: 10.1086/340491
|View full text |Cite
|
Sign up to set email alerts
|

Galactic Starburst NGC 3603 from X‐Rays to Radio

Abstract: 1Ddpartementde physique,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
108
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(125 citation statements)
references
References 29 publications
16
108
1
Order By: Relevance
“…We estimated for this source an X-ray luminosity of 2 × 10 30 erg s −1 assuming a plasma temperature kT = 2.16 keV, as for all the other sources in our sample. This luminosity corresponds to L X /L bol ∼ (0.5−1) × 10 −8 , which is about one order of magnitude lower than typically observed for older massive stars (Sciortino et al 1990), although there is a large scatter (±1 dex) on the L X /L bol relation for massive stars (e.g., Moffat et al 2002). The assumed X-ray plasma temperature for S106 IRS 4 is however likely too high for an early type star.…”
Section: S106 Irsmentioning
confidence: 71%
“…We estimated for this source an X-ray luminosity of 2 × 10 30 erg s −1 assuming a plasma temperature kT = 2.16 keV, as for all the other sources in our sample. This luminosity corresponds to L X /L bol ∼ (0.5−1) × 10 −8 , which is about one order of magnitude lower than typically observed for older massive stars (Sciortino et al 1990), although there is a large scatter (±1 dex) on the L X /L bol relation for massive stars (e.g., Moffat et al 2002). The assumed X-ray plasma temperature for S106 IRS 4 is however likely too high for an early type star.…”
Section: S106 Irsmentioning
confidence: 71%
“…Moffat et al (2002) reported X-ray luminosities of three WN6ha stars in NGC 3603 as observed with ACIS-I. For NGC 3603 stars A1, B and C, these authors obtain >10 34 , 2-3 × 10 33 and >4 × 10 34 erg s −1 respectively (the lower limits for stars A1 and C are due to pile-up in the Chandra data).…”
Section: X-ray Emission From Wr 20amentioning
confidence: 81%
“…For NGC 3603 stars A1, B and C, these authors obtain >10 34 , 2-3 × 10 33 and >4 × 10 34 erg s −1 respectively (the lower limits for stars A1 and C are due to pile-up in the Chandra data). Although it remains to be established what fraction of their X-ray fluxes arises from colliding wind interactions, we note that the two X-ray brightest Wolf-Rayet objects in NGC 3603 are either confirmed or suspected binary systems (see the discussion in Moffat et al 2002). Since the wind properties of the components of WR 20a are more typical of extreme Of stars than of classical Wolf-Rayet stars, we compare the observed X-ray luminosity of WR 20a also to the empirical L X -L bol relation for OB stars derived by Berghöfer et al (1997).…”
Section: X-ray Emission From Wr 20amentioning
confidence: 93%
“…Lang 2003;Moffat et al 2002;Setia Gunawan et al 2003). The stellar radio sources are blue, A&A 511, A58 (2010) Fig.…”
Section: Identification Of Radio Starsmentioning
confidence: 96%